Would a zero-growth economy be achievable and be sustainable? - Giuseppe Fontana; Malcolm Sawyer (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2022)
The argument for zero economic growth comes from environmental sustainability considerations. But can zero economic growth be achieved in a demand-driven economy? What are the macro conditions under which it could be achieved, and would it be sustainable? There is a range of issues which would have to be resolved if a zero-growth economy is to be achieved and sustained. The first concerns the routes through which net investment would be constrained to zero. The second relates to the issue of whether the rate of profit would go to zero in a zero-growth economy, and hence the question of whether zero growth is compatible with capitalism. Or are there routes such as continual budget deficits and reduced savings which would maintain a non-zero rate of profit? And then whether budget deficits and reduced savings are sustainable. The third relates to the nature of the banking system (and any related monetary growth imperative) and the implications of sustained zero/negative rates of interest. An outcome of zero growth would obviously involve a constant level of GDP (though not necessarily of economic and social activity). Would there be forces which generate a supply of labour larger than 'full employment', and would productivity continue to rise?
Keywords: 330; zero growth; investment; profits; employment; budget deficitO40; Q56